Zambia scaling week: Workshop report - Ewell, Hanna; Kagabo, Desire; Wapamesa, Agrey; Mwale, Emely; Pele, Winnie; Chinembiri, Evans; Ouedraogo, Mathieu (2025)
The AICCRA Zambia Scaling Week workshop, held at the Urban Hotel in Lusaka 9-11th July 2025, focused on advancing the responsible and inclusive scaling of Climate Information Services (CIS) and Climate-Smart Agriculture (CSA) solutions to enhance resilience among smallholder farmers in Zambia. It brought together 18 people (7 of whom were women) from various organizations, including the Ministry of Agriculture’s Extension and Technical Departments, the Ministry of Green Economy and Environment’s Meteorological Department (ZMD), the University of Zambia, Greencare Eco Solutions, Green Giraffe Zambia, Agricomm Media and Marketing under the Institute of Agriculture Communication Research, Mediae and BongoHive. The objective of the workshop was to engage in capacity sharing on the theory and practice of scaling, as well as to support the Zambia cluster in understanding and operationalizing the scaling framework of the AICCRA project by assessing CIS and CSA bundles and developing corresponding preliminary scaling pathways. Regarding methodological approaches, presentations were used to explain principles, with small groups' work and plenary discussions in a participative atmosphere. Based on the concepts and principles shared, participants reflected on their visions, the barriers they face, and accelerators or enabling factors to overcome them, and established roadmaps for four innovations: the digital participatory integrated climate services for Africa tool (e-PICSA), eco-conscious snack products, organic fertilizer and a newly planned weather channel. Key lessons include the value of bundling, coopetition, gender-responsive delivery, and embedding solutions in national systems to ensure sustainability, equity, and long-term resilience